Early growth, green manure yield and soil properties of selected trees and shrubs on wetland paddy bunds of Kerala - Chirakkal, Arya; Asha K. Raj; Kunhamu T. K; Jamaludheen V; Divya Vijayan V (Indian Journal of Agroforestry, 2025)
Rice, the staple food in Kerala, is currently facing a significant production deficit, meeting only one-fifth of the annual requirement. Green leaf manuring offers a promising, cost-effective, and eco-friendly solution to enhance productivity. Traditional green leaf manuring practices in Kerala have been abandoned due to the scarcity of conventional green leaves, along with increased labour and transportation costs. To address these constraints, this study proposes a feasible eco-friendly approach: cultivating green leaf biomass of trees and shrubs in rice bunds and maintaining them as 1 m hedges through regular lopping. Gliricidia (Gliricidia sepium), garuga (Garuga pinnata), sesbania (Sesbania grandiflora), calliandra (Calliandra calothyrsus), terminalia (Terminalia arjuna), mulberry (Morus indica), gmelina (Gmelina arborea), red gram (perennial) (Cajanus cajan), and cassia (Cassia siamea) were planted in paddy bunds at spacing of 1m, in Randomized Block Design with three replications. The results of the study revealed that sesbania exhibited the highest annual biomass yield (5.45 kg plant-1), followed by red gram (4.10 kg plant-1), gliricidia (3.26 kg plant-1), and arjuna (2.54 kg plant-1) during the initial year of planting. Conversely, cassia and gmelina displayed slower growth rates, while garuga and gmelina exhibited lower survival rates. Garuga had a survival rate of only 10 per cent, rendering it unsuitable for bund planting in paddy fields. Furthermore, a significant decrease in available nitrogen content was noted in paddy soils beneath mulberry, indicating its competitive nature. Plant species such as sesbania, red gram, cassia, arjuna, and gliricidia, which demonstrated robust productivity and resilience, are considered excellent choices for planting on wetland paddy bunds.